Occupational Safety Risk Analysis in Onshore and Offshore Pipe Coating Processes at Wasco Coating Middle East - Edy Kurniawan; Syahrir; Nurianti HS (LP2M IAIN Palopo, 2025)
This study aims to analyze occupational safety risks in the onshore and offshore pipe coating process at Wasco Coating Middle East. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, field observations, and documentation. Informants consisted of field workers, supervisors, and HSE officers selected purposively. Data analysis was conducted using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results show that the main risks in the coating process include exposure to hazardous chemicals, high noise, potential physical accidents, and ergonomic risks. Although the company has implemented an occupational safety system, its effectiveness is still influenced by worker compliance, production pressure, and the complexity of the offshore project. This study recommends strengthening the safety culture and increasing risk-based training to reduce the potential for workplace accidents.